Addressing health inequity during the COVID-19 pandemic through primary health care and public health collaboration: a multiple case study analysis in eight high-income countries - Vanden Bossche, Dorien; Zhao, Q. Jane; Ares-Blanco, Sara; Peña, Maria Pilar Astier; Decat, Peter; Kondo, Naoki; Kroneman, Madelon; Nishioka, Daisuke; Petrazzuoli, Ferdinando; Rortveit, Guri; Schaubroeck, Emmily; Stark, Stefanie; et al. (International Journal For Equity in Health, 2023)
Background: The COVID-19 pandemic substantially magnified the inequity gaps among vulnerable populations. Both public health (PH) and primary health care (PHC) have been crucial in addressing the challenges posed by the pandemic, especially in the area of vulnerable populations. However, little is known about the intersection between PH and PHC as a strategy to mitigate the inequity gap. This study aims to assess the collaboration between PHC and PH with a focus on addressing the health needs of vulnerable populations during the COVID-19 pandemic across jurisdictions. Methods: We analyzed and compared data from jurisdictional reports of COVID-19 pandemic responses in PHC and PH in Belgium, Canada (Ontario), Germany, Italy, Japan, the Netherlands, Norway, and Spain from 2020 to 2021. Results: Four themes emerge from the analysis: (1) the majority of the countries implemented outreach strategies targeting vulnerable groups as a means to ensure continued access to PHC; (2) digital assessment in PHC was found to be present across all the countries; (3) PHC was insufficiently represented at the decision-making level; (4) there is a lack of clear communication channels between PH and PHC in all the countries. Conclusions: This study identified opportunities for collaboration between PHC and PH to reduce inequity gaps and to improve population health, focusing on vulnerable populations. The COVID-19 response in these eight countries has demonstrated the importance of an integrated PHC system. Consequently, the development of effective strategies for responding to and planning for pandemics should take into account the social determinants of health in order to mitigate the unequal impact of COVID-19. Careful, intentional coordination between PH and PHC should be established in normal times as a basis for effective response during future public health emergencies. The pandemic has provided significant insights on how to strengthen health systems and provide universal access to healthcare by fostering stronger connections between PH and PHC.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Collaboration; COVID-19; Equity; Primary health care; Public health; Vulnerable populations

Dipsticks and point-of-care Microscopy to reduce antibiotic use in women with an uncomplicated Urinary Tract Infection (MicUTI): protocol of a randomised controlled pilot trial in primary care - Kurotschka, Peter K.; Borgulya, Gábor; Bucher, Eva; Endrich, Isabell; Figueiras, Adolfo; Gensichen, Jochen; Hay, Alastair D.; Hapfelmeier, Alexander; Kretzschmann, Christian; Kurzai, Oliver; Lam, Thien Tri; Massidda, Orietta; et al. (BMJ Open, 2024)
Introduction Uncomplicated urinary tract infections (uUTIs) in women are common infections encountered in primary care. Evidence suggests that rapid point-of-care tests (POCTs) to detect bacteria and erythrocytes in urine at presentation may help primary care clinicians to identify women with uUTIs in whom antibiotics can be withheld without influencing clinical outcomes. This pilot study aims to provide preliminary evidence on whether a POCT informed management of uUTI in women can safely reduce antibiotic use. Methods and analysis This is an open-label two-arm parallel cluster-randomised controlled pilot trial. 20 general practices affiliated with the Bavarian Practice-Based Research Network (BayFoNet) in Germany were randomly assigned to deliver patient management based on POCTs or to provide usual care. POCTs consist of phase-contrast microscopy to detect bacteria and urinary dipsticks to detect erythrocytes in urine samples. In both arms, urine samples will be obtained at presentation for POCTs (intervention arm only) and microbiological analysis. Women will be followed-up for 28 days from enrolment using self-reported symptom diaries, telephone follow-up and a review of the electronic medical record. Primary outcomes are feasibility of patient enrolment and retention rates per site, which will be summarised by means and SDs, with corresponding confidence and prediction intervals. Secondary outcomes include antibiotic use for UTI at day 28, time to symptom resolution, symptom burden, number of recurrent and upper UTIs and re-consultations and diagnostic accuracy of POCTs versus urine culture as the reference standard. These outcomes will be explored at cluster-levels and individual-levels using descriptive statistics, two-sample hypothesis tests and mixed effects models or generalised estimation equations. Ethics and dissemination The University of Würzburg institutional review board approved MicUTI on 16 December 2022 (protocol n. 109/22-sc). Study findings will be disseminated through peer-reviewed publications, conferences, reports addressed to clinicians and the local citizen’s forums.
CRIS-Team Scopus Importer:2024-04-26

Effectiveness of an online asthma education program in adults with asthma in general practice: Results from a cluster randomised controlled trial - Eck, Stefanie; Baumgärtel, Andrea; Hapfelmeier, Alexander; Linde, Klaus; Sanftenberg, Linda; Stark, Stefanie; Schultz, Konrad; McClatchey, Kirstie; Pinnock, Hilary; Schneider, Antonius (Respiratory Medicine, 2025)
Background: Asthma education programs (AEPs) are crucial to improving patient outcomes, but few patients participate. Therefore, an online asthma education program (electronic AEP, eAEP) has been developed. We aimed to investigate the effectiveness of the eAEP in adults with asthma in terms of asthma knowledge, symptom control and emergency treatments. Methods: In a cluster randomised controlled trial, general practitioner (GP) practices were randomly assigned to either access to the intervention (eAEP), or usual care (UC) control. Outcomes were assessed at baseline, two weeks, three and six months. Primary endpoint was the difference in Asthma Knowledge Test (AKT) scores after completion of the eAEP/UC. Secondary outcomes included symptom control (Asthma Control Test, ACT) and emergency treatments. Findings: 62 patients from 10 intervention practices and 46 patients from 11 control practices were analysed. The intervention group had significantly greater improvements in mean AKT scores (between-group adjusted mean difference (AMD), 9.3 (95 % CI 6.3–12.3), p < 0.001) at the primary endpoint. Differences remained relatively stable during the six-month follow-up. Between-group AMD in the ACT was 1.4 (95 % CI -0.1-2.8, p < 0.062) three months after the eAEP/UC and 1.6 (95 % CI 0.2–2.9, p < 0.023) at study end. More intervention group patients demonstrated the inhalation technique correctly (98 % vs. 79 %, p = 0.007), received peak expiratory flow instructions (94 % vs. 32 %, p < 0.001) and an asthma action plan (96 % vs. 50 %, p < 0.001). Interpretation: The eAEP was effective in improving knowledge over six months and showed beneficial effects on symptom control. The eAEP may contribute to improved asthma care in GP settings.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Asthma; Asthma knowledge; Asthma self-management; Digital intervention; Primary care; Symptom control

Effectiveness of an online education program for asthma patients in general practice: study protocol for a cluster randomized controlled trial - Eck, Stefanie; Hapfelmeier, Alexander; Linde, Klaus; Schultz, Konrad; Gensichen, Jochen; Sanftenberg, Linda; Kühlein, Thomas; Stark, Stefanie; Gágyor, Ildikó; Kretzschmann, Christian; Schneider, Antonius (BMC Pulmonary Medicine, 2022)
Background: Asthma education programs (AEPs) have been shown to increase quality of life and reduce emergency treatments and hospital admissions. Despite the proven benefits, only a minority of asthma patients attend such programs. To increase the number of educated patients, an online education program (electronic AEP, eAEP) for asthma patients has been developed. The present study aims to investigate the effectiveness of the eAEP in terms of asthma knowledge, asthma control and emergency treatments in general practice settings. Methods: This is a cluster randomized controlled trial including 100 patients with bronchial asthma from 20 general practices in Bavaria, Germany. General practices will be randomly assigned to either the intervention or control group. Patients in the intervention group will receive access to the eAEP and instructions to complete this program within two weeks. Patients in the control group will receive usual care including a referral to face-to-face AEP (fAEP) by a certified primary care physician or a pulmonologist according to guideline recommendations. Furthermore, patients of both the intervention and control groups will be invited to a follow-up consultation in their general practice after completion of the eAEP and fAEP (three weeks and twelve weeks after study inclusion, respectively) to discuss any open issues. Outcomes for both groups will be assessed at baseline (t0), after two weeks (t1), three months (t2) and six months (t3). The primary outcome is the comparison of asthma knowledge gain between intervention and control groups after completion of the eAEP (two weeks after study inclusion) and fAEP (twelve weeks after study inclusion), respectively. Secondary outcomes include asthma control, frequency of emergency treatments, patient autonomy as well as attitudes towards asthma medication. Discussion: The results of the present trial will provide knowledge about the effectiveness of an online education program for asthma patients compared to usual care in primary care. Trial registration: German Clinical Trials Register (DRKS), DRKS00028805. Registered 22 April 2022.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Asthma; Asthma knowledge; Cluster randomized controlled trial; Digital intervention; Patient education; Primary care; Self-management

Expectations of general practitioners on a practice based research network in Germany- a qualitative study within the Bavarian Research Practice Network (BayFoNet) - Sanftenberg, Linda; Stofella, Julia; Mayr, Katharina; Nassehi, Armin; Härdtlein, Annette; Stark, Stefanie; Kühlein, Thomas; Kurotschka, Peter Konstantin; Gágyor, Ildikò; Eck, Stefanie; Schneider, Antonius; Bößenecker, Melanie; et al. (BMC Primary Care, 2024)
Background: Despite general practitioners' (GPs') key role in Germany`s primary health care, clinical research in general practice is scarce. Clinical research is mainly conducted at inpatient facilities, although their results are rarely transferable. German GPs have no extra time or funding for research, as well as limited research training. To support clinical research in German primary health care, practice-based research networks (PBRNs) are developed. As they will be based on an active involvement of GPs, we need more information on GPs` participation-readiness. The aim of this study was to explore facilitators and barriers to participation in the Bavarian Research Practice Network (BayFoNet) from the GPs`perspective before clinical trials will be performed. Methods: We have performed semi-structured qualitative interviews with a purposive sample of 20 Bavarian GPs in 2022 under the application of the consolidated framework for implementation research (CFIR). Transcriptions were analysed according to Kuckartz` qualitative content analysis. The five domains of the CFIR framework served as initial deductive codes. Results: N = 14 interviewees already agreed to participate in BayFoNet, whereas n = 6 interviewees opted not to participate in BayFoNet at the time of data collection. Main facilitators to conduct clinical research within BayFoNet were the motivation to contribute to evidence strength and quality in general practice, professional development and training of practice staff, as well as networking. Barriers for an active participation were bad experiences with previous clinical studies and lack of resources. Conclusions: PBRNS in Germany have to be promoted and the entire practice team has to be involved at an early stage of development. Professional training of general practice staff and a living network might enhance engagement. Participatory approaches could help to develop acceptable and feasible study designs. Furthermore, PBRNs should support patient recruitment and data collection in general practices and disseminate the results of their research projects regularly to maintain GPs` engagement. Trial registration: DRKS00028805, NCT05667207.
CRIS-Team Scopus Importer:2024-01-12
Keywords: General practice; Implementation science; Participatory research; Practice based research network; Primary health care

Experiences of general practice teams and their patients with clinical research-a mixed-methods process evaluation of the Bavarian Research Practice Network (BayFoNet) - Sanftenberg, Linda; Schnaidt, Anna Lena; Eck, Stefanie; Schneider, Antonius; Bucher, Eva; Kurotschka, Peter Konstantin; Gágyor, Ildikó; Klanke, Merle; Stark, Stefanie; Kühlein, Thomas; Walter, Fabian; Roos, Marco; et al. (BMC Primary Care, 2025)
BACKGROUND: Practice-based research networks (PBRNs) have been implemented to support clinical research in German general practice since 2020. General practitioners (GPs) are often critical concerning the feasibility of clinical trials. Among others, high workload, lack of resources in GP teams and little acceptance of the trial requirements by the patients are assumed barriers. Therefore, the aim of this study was to evaluate the perspectives of the GP teams and their patients on the set up of BayFoNet during the implementation of the two pilot cluster-randomized trials to improve this collaboration on a sustainable basis. METHODS: GPs and medical assistants (MAs) were interviewed using semi-structured interviews based on the Consolidated Framework for Implementation Research. Implementation research and verbatim transcripts were analyzed using qualitative content analysis. Patient attitudes were evaluated quantitatively with questionnaires based on the theoretical domains framework using descriptive statistics. RESULTS: A total of 15 GPs and 15 MAs were interviewed, and 109 complete patient questionnaires were returned. Main facilitators for GPs' active participation in clinical research were networking as well as active participation of GP teams at different levels of the research process. Increased awareness concerning PBRNs might promote a lively network. From the GPs' perspective, lack of motivation among MAs and patients was a perceived barrier to support clinical research in general practice. MAs emphasized their own increase in knowledge and competence as well as the importance of clinical research for improved patient care. In contrast to the GPs, most MAs were not aware of BayFoNet as a network structure. The surveyed patients rated their own capabilities and opportunities to actively participate in the pilot studies as very good. Prior to the implementations of the interventions, some patients experienced some difficulty in defining clear goals for their own participation. DISCUSSION: Increased awareness concerning PBRNs might promote a lively network. Target-group specific dissemination strategies as well as opportunities for GP teams and their patients to participate in clinical research should be elaborated. This might increase the feasibility of clinical trials and the motivation of all participants to conduct clinical trials in general practice. TRIAL REGISTRATION: Pilot cluster-randomized trial 1 (MicUTI) was prospectively registered on December 19, 2022 at www. CLINICALTRIALS: gov (NCT05667207); Pilot cluster-randomized trial 2 (IMONEDA) was prospectively registered on April 22, 2022 at www.bfarm.de (DRKS00028805).
CRIS-Team Scopus Importer:2025-03-21
Keywords: General practice; Implementation science; Participatory research; Practice based research network; Primary health care

Has the COVID-19 Pandemic Led to Changes in the Tasks of the Primary Care Workforce? An International Survey among General Practices in 38 Countries (PRICOV-19) - Groenewegen, Peter; Van Poel, Esther; Spreeuwenberg, Peter; Batenburg, Ronald; Mallen, Christian; Murauskiene, Liubove; Peris, Antoni; Petre, Benoit; Schaubroeck, Emmily; Stark, Stefanie; Sigurdsson, Emil L.; Tatsioni, Athina; et al. (International Journal of Environmental Research and Public Health, 2022)
The COVID-19 pandemic has had a large and varying impact on primary care. This paper studies changes in the tasks of general practitioners (GPs) and associated staff during the COVID-19 pandemic. Data from the PRICOV-19 study of 5093 GPs in 38 countries were used. We constructed a scale for task changes and performed multilevel analyses. The scale was reliable at both GP and country level. Clustering of task changes at country level was considerable (25%). During the pandemic, staff members were more involved in giving information and recommendations to patients contacting the practice by phone, and they were more involved in triage. GPs took on additional responsibilities and were more involved in reaching out to patients. Problems due to staff absence, when dealt with internally, were related to more task changes. Task changes were larger in practices employing a wider range of professional groups. Whilst GPs were happy with the task changes in practices with more changes, they also felt the need for further training. A higher-than-average proportion of elderly people and people with a chronic condition in the practice were related to task changes. The number of infections in a country during the first wave of the pandemic was related to task changes. Other characteristics at country level were not associated with task changes. Future research on the sustainability of task changes after the pandemic is needed.
CRIS-Team Scopus Importer:2022-12-09
Keywords: COVID-19; general practice; general practitioners; international comparison; PRICOV-19; primary care workforce; primary health care; quality of care; task changes

Partizipation in der Palliativforschung - Heckel, Maria; Gehrmann, Jan; Burggraf, Larissa; Stark, Stefanie; Ullrich, Anneke (Pflege Zeitschrift, 2022)
Partizipation gewinnt im Gesundheitswesen an Bedeutung. Inwiefern und zu welchen Fragen findet Partizipation in der Palliativforschung statt? Eine Online-Befragung von Forschungseinrichtungen (März bis Juni 2022) zeigt, dass in acht von zehn Einrichtungen Fachpersonal, Angehörige sowie Patient*innenvertreter*innen, teils sporadisch, teils regelmäßig, partizipieren - mitbestimmend, mitwirkend und beratend, etwa bei Themen wie Versorgungsstrukturen und -formen. Evaluationen zur erwarteten Qualitätsverbesserung und erleichterten Verbreitung von Forschungsergebnissen fehlen. Partizipation findet ohne Einfluss auf die Themen- und Methodenwahl statt, was aber für die Versorgungspraxis gewinnbringend und durch die Einrichtung permanenter Partizipationsgruppen umsetzbar wäre. Fachbereichsübergreifende Erforschung von Partizipationsformaten lässt konzeptionelle und ressourcenbezogene Vorteile erwarte

Recruitment, data collection, participation rate, and representativeness of the international cross-sectional PRICOV-19 study across 38 countries - Tatsioni, Athina; Groenewegen, Peter; Van Poel, Esther; Vafeidou, Kyriaki; Assenova, Radost; Hoffmann, Kathryn; Schaubroeck, Emmily; Stark, Stefanie; Tkachenko, Victoria; Willems, Sara (BMC Primary Care, 2023)
Background: Recruitment for surveys has been a great challenge, especially in general practice. Methods: Here, we reported recruitment strategies, data collection, participation rates (PR) and representativeness of the PRICOV-19 study, an international comparative, cross-sectional, online survey among general practices (GP practices) in 37 European countries and Israel. Results: Nine (24%) countries reported a published invitation; 19 (50%) had direct contact with all GPs/GP practices; 19 (50%) contacted a sample of GPs /GP practices; and 7 (18%) used another invitation strategy. The median participation rate was 22% (IQR = 10%, 28%). Multiple invitation strategies (P-value 0.93) and multiple strategies to increase PR (P-value 0.64) were not correlated with the PR. GP practices in (semi-) rural areas, GP practices serving more than 10,000 patients, and group practices were over-represented (P-value < 0.001). There was no significant correlation between the PR and strength of the primary care (PC) system [Spearman’s r 0.13, 95% CI (-0.24, 0.46); P-value 0.49]; the COVID-19 morbidity [Spearman’s r 0.19, 95% CI (-0.14, 0.49); P-value 0.24], or COVID-19 mortality [Spearman’s r 0.19, 95% CI (-0.02, 0.58); P-value 0.06] during the three months before country-specific study commencement. Conclusion: Our main contribution here was to describe the survey recruitment and representativeness of PRICOV-19, an important and novel study.
CRIS-Team Scopus Importer:2024-12-16
Keywords: COVID-19; Family medicine; PRICOV-19 study; Primary health care; Quality of care; Recruitment; Representativeness

“The measures taken by the government overburdened the daily practice” – insights of the PRICOV-19 study on German general practitioners in times of COVID-19 - Stark, Stefanie; Schaubroeck, Emmily; Kluge, Marie; Burggraf, Larissa; Roos, Marco; Borowski, Eve; Van Poel, Esther; Willems, Sara; Kühlein, Thomas; Hueber, Susann; Werner, Felix (BMC Primary Care, 2023)
Background: The international study PRICOV-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on German general practitioners during the second wave of the COVID-19 pandemic. This paper addresses the following research questions: (1) How were changes in tasks on primary care and patient treatment perceived by GPs?, (2) What was the role of GPs during the pandemic, and how was their wellbeing?, (3) How did GPs perceive health policy measures?, and, (4) What influenced the attitudes of GPs on health policy measures? Methods: This study pursues a multi-country cross-sectional design. Data collection took place throughout Germany from 01.02. to 28.02.2021 with a quantitative online questionnaire consisting of 53 items. The questionnaire was analysed through descriptive and inferential analyses using correlation and multiple regression models. Results: The response rate was 20.4% (n = 349). The respondents were mainly GPs (59.6%) in single practices (62.5%) with a mean work experience of 15 to 20 years. GPs experienced a change in their work and practice organisation (80.3%). They felt a high responsibility (70.6%) and found their work has become more meaningful to them (76%). They also saw a lack of political support (75.2%) and that the measures taken by the government overburdened the daily practice (66.4%). Not many GPs were at risk of being distressed (53.4%) but rated the health policies rather negatively (60%). The multiple regression showed, the more GPs were exposed to risk of distress, the worse they assessed the government's measures. Conclusion: GPs perceived their work as relevant and felt confident they could fulfil their tasks, but noticed that health policy initially hardly supported the outpatient sector. Health policies should increase their competence in relation to primary care, ensure its needs and consider an active inclusion of GPs in preparedness plans.
CRIS-Team Scopus Importer:2023-10-20
Keywords: COVID-19; General practitioners; Health policy; PRICOV-19; Primary health care; Quality of care; Wellbeing

The patient satisfaction in primary care consultation—Questionnaire (PiC): An instrument to assess the impact of patient-centred communication on patient satisfaction - Stark, Stefanie; Worm, Lukas; Kluge, Marie; Roos, Marco; Burggraf, Larissa (PLoS ONE, 2021)
Background Primary care consultation is significantly influenced by communication between the General Practitioner (GP) and their patients. Hypothesising that patient satisfaction can be tested based on an expectation-experience comparison, the aim of this article is to discuss the influence of communication on patient satisfaction. Methods A standardised questionnaire was developed striving for a universal primary care survey tool that focuses on patient satisfaction in the context of patient-centred-communication. The sample consisted of 14 German GPs with 80 patients each (n = 1120). Due to the inclusion in an overarching cluster-randomised-study (CRT), the medical practices to be examined were divided into intervention and control groups. The intervention was developed as a reflective training on patient-centred communication. Results The results in the present sample show no correlation between patient-centred-communication and patient satisfaction. There are also no significant differences between the intervention and control group. Discussion The results raise the question to what extent patient satisfaction can be shaped significantly through patient-centred-communication. The presented project represents part of the basic research in general medical care research and contributes to the transparent processing of theoretical assumptions. With the results described here, communication models with a focus on patient centredness can be evaluated with regard to their practical relevance and transferability.
CRIS-Team Scopus Importer:2021-07-30

Was braucht es, um forschungsfit zu sein? Fokusgruppendiskussionen mit Hausärzt*innen und Medizinischen Fachangestellten - Wolf, Florian; Klanke, Merle; Klein, Astrid Alexandra; Kuschick, Doreen; Lingner, Heidrun; Löscher, Susanne; Stark, Stefanie; Mergenthal, Karola (Zeitschrift für Allgemeinmedizin, 2024)
Background: Academic institutes of general practice and practice-based research networks are constantly faced with the challenge of how they can actively and sustainably involve primary care practice teams in research projects. There are currently no standardized research readiness criteria in Germany. Objectives: What do primary care practice teams need to be able to participate in research projects? Materials and methods: Three focus group discussions were conducted with a total of 13 general practitioners (GPs) and 12 medical assistants (MAs) in February and March 2023. Prerequisites for perceived research readiness were explored and discussed using three study designs. A qualitative content analysis according to Kuckartz was conducted on the basis of the observation protocols and the whiteboard recordings. Results and conclusion: Both study-specific and cross-study prerequisites were identified. In order to feel research ready, not only do GPs and MAs need the support and coordination of those responsible for the study, but their own willingness and the corresponding resources must also be available within the practice team. The findings of the focus group discussions will be incorporated into the development of a research-ready concept for practice-based research networks in Germany.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Attitudes; Practice-based research network; Prerequisites; Primary care; Research participation

“What else to say?”-Primary health care in times of COVID-19 from the perspective of German general practitioners: An exploratory analysis of the open text field in the PRICOV-19 study - Stark, Stefanie; Kluge, Marie; Schaubroeck, Emmily; Werner, Felix; van Poel, Esther; Willems, Sara; Roos, Marco; Kühlein, Thomas; Burggraf, Larissa (PLoS ONE, 2023)
Background The international collaboration study PRICOV-19 -Primary Health Care in times of COVID-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on the subjective perceptions of general practitioners on primary health care and the impact of political measures during the second wave of the COVID-19 pandemic. Within this survey, the “open text field” of the questionnaire was utilised remarkably frequently and extensively by the respondents. It became clear that the content that was named needed to be analysed in an exploratory manner. Accordingly, this paper addresses the following question: What preoccupies general practitioners in Germany during COVID-19 that we have not yet asked them enough? Methods The data collection took place throughout Germany from 01.02.2021 to 28.02.2021with a quantitative online questionnaire consisting of 53 items arranged across six topics as well as an “open text field” for further comments. The questionnaire's open text field was analysed following the premises of the qualitative content analysis. Results The topics discussed by the respondents were: insufficient support from health policies, not being prioritised and involved in the vaccination strategy, feeling insufficient prepared, that infrastructural changes and financial concerns threatened the practice, and perceiving the own role as important, as well as that health policies affected the wellbeing of the respondents. One of the main points was the way general practitioners were not sufficiently acknowledged for their contribution to ensuring high-quality care during the pandemic. Discussion German general practitioners perceived their work and role as highly relevant during the COVID-19 pandemic. In controversy with their perception, they described political conditions in which they were the ones who contributed significantly to the fight against the pandemic but were not given enough recognition.
CRIS-Team Scopus Importer:2023-03-31